Application of a HEC-HMS model on event-based simulations in a tropical watershed - Miyuru Bandara Gunathilake; Pushpika Panditharathne; Anura Shantha Gunathilake; Narada Warakagoda (Engineering and Applied Science Research, 2020)
The upper reaches of the Seethawaka River in Sri Lanka lie in the highest rainfall region of the country. The development of a rainfall-runoff model for the Seethawaka River will essentially aid in reducing vulnerability to disastersthathappen due to extreme rainfall events in the area. This research paper describes a case study of an event-based streamflow simulation approach for the Seethawaka River in the Kegalle administrative district of Sri Lanka using a conceptually-based, deterministic and semi-distributed Hydrologic Engineering Center-Hydrologic Modeling System (HEC-HMS). The main aim of this study was to examine the most reliable combination of precipitation loss and baseflow methods to simulate streamflow in the study area. Six combinations of precipitation loss methods, direct runoff methods, baseflow methods and routing methods were separately checked to determine the most effective method. Among the various combinations of precipitation loss and baseflow methods simulated, the Soil Conservation Service Curve Number method (SCS_CN) and the non-linear Boussinesq method performed fairly well with Clark unit hydrograph, Muskingum and lag methods. The values of statistical indicators and graphical observations revealed that the model developed through this study is capable of simulating peak discharges and timing the occurrence of peaks fairly well. Therefore, this model will greatly help in providing early warnings to the lower reaches of Seethawaka during extreme rainfall events.